DESKRIPSI PELAKSANAAN E-LEARNING DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MASA COVID-19 TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA KELAS XII MIA - Ariska, Devi; Yustina, Yustina; Mahadi, Imam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to describe the infrastructure in the implementation of e-learning and the relationship between e-learning and problem-based learning models on the creative thinking skills of class XII students. This research is a qualitative descriptive study. The subjects in this study were students of class XII MIA SMA Islam As-Shofa Pekanbaru. The data collection technique is a survey using an observation sheet. The results of the study provide some information. First, SMA Islam As-Shofa has adequate facilities and infrastructure to support the implementation of e-learning, which consists of hardware, software, and a learning community. Second, the implementation of e-learning runs well using the PBL model on the creative thinking skills of class XII MIA students of SMA Islam As-Shofa Pekanbaru.Key Words: E-Learning, Creative Thinking, Problem Based Learning